(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This paper provides a critical analysis of the recent Italian law relating to Medical responsability. The law n. 24 of 2017 (so-called Gelli), welcomed with great enthusiasm by the medical class, intervenes, to less than five years from the law Balduzzi, on the statute of the responsability in sanitary circle. The new physiognomy of the negligence of the doctor is based on discipline of the guide lines inside which to potentially individualize the binding recommendations for the operators the sanitary professions and on the introduction of double track between contractual liability of the sanitary structure and the independent contractor and extracontractual liability of the doctor related to the hospital. The analisy presented emphasises the gaps and the contradictions of law which also from the formulation chosen by the legislator.